Penghijrahan buruh India ke Pulau Pinang: Kajian mengenai corak migrasi dan pengaruh sosio-ekonomi sebelum tahun 1930 Indian labour migration to Penang: Study on the patterns of migration and socio-economic impact before the year 1930 - Rathakrishnan, Mohan (UKM, 2017)
The arrival of Indian laborers to Penang occurs rapidly during the British occupation. Many Indian workers were brought in by 1820s. The economic and social crisis in India have affected the demographics of Penang following the arrival of Indian labor in 19th century. Penang as Straits Settlements state was a well-known port in Southeast Asia. Labor from India was used by the British to develop the plantations of rubber, oil and transportation. There are various aspects that affect the lifestyle of Indian labor, such as politics, cultural belief, economic and social. However, this study focuses on the inclusion of Indian labor and migration patterns after the opening of Penang and social influences such as the caste system, economic activities such as plantation workesrs in the plantation sector which is practiced in India for Indian workers living in Penang. In addition to the caste problem, this study also explained injustice zamindar against the Indian labor. Reference for this article consists of oral sources, documents, manuscipt and books. The findings of this study show that before 1930, the influence of social (caste system) and employment practices in India still has an influence on Indian workers in Penang. The scope of this study includes the social impact of the caste system and the economy as well as Indian labor migration patterns involving agents working under the system of “indenture”and “kangani”. In conclusion, this article describes the social and economic impact from India against Indian in Penang before 1930.